The impact of inteprofessional education to health students’ collaborative competencies - Desak Ketut Ernawati; Desak Ketut Indrasari Utami (International Journal of Evaluation and Research in Education (IJERE), 2020)
One of the aims of Interprofessional education (IPE) is to foster collaboration amongst healthcare professionals. IPE has been adopted at Udayana University by involving seven health courses at Udayana University, Bali, Indonesia. These students were assigned to 49 groups which composed the seven health course students. They learned working in collaboration from cases identified in the community. The activities spanned for five semesters. At the beginning of their activities the students received interprofessional collaboration competencies attainment survey (ICCAS). The survey has been validated in the population and has two collaborative competencies, namely communication and collaboration. This was a report of ICCAS employment in Semester III dan IV of the first cohort of IPE Program at Udayana University. 138 students completed the survey in both semesters. A paired-sample t-test was conducted to compare the mean score differences of collaboration and communication in the first and second semesters of attending IPE learning. Whilst, there was no significant differences on the mean score for communication, there was a significant difference in the mean score for pre and post collaboration (94.7±9.7) and (91.0±10.8); t(130)=3.379, p=0.001. These results suggest that the collaboration competencies amongst the seven health courses students reduced after one semester attending IPE activities. These findings indicated that the study design and learning tasks should be amended to ensure students gain the most of their learning in collaboration.